Intrinsict Elements of Bidadari Paderi - Hayu Uswatun Khasanah; Ega Dwi Adis; Dewi Rukayah; Madha Vesakha; Tigor Permana (Universitas Islam Balitar, 2017)
The research entitled “Konflik Sosial dalam Novel Bidadari Paderi Karya Saiful ArdiImam.” Social conflict is prominently presented in Saiful Ardi Imam’s Bidadari Paderi.Based on the background of the story, the research problems are formulated as how theintrinsic elements are and what social conflicts have happened within the story. Thisresearch aims at describing the intrinsic elements covering plot, characterization, andsetting and describing the social conflict depicted. Theoretically, this research is expectedto bring benefits toward the development of literary studies, particularly the sociology ofliterature. Practically, the research is expected to ease the readers understanding onSaiful Ardi Imam’s Bidadari Paderi. The object of this research is the novel entitledBidadari Paderi that will be analyzed using sociology of literature. The analysis techniqueemployed in this research is to describe the classifed data in order to figure out therelations of each intrinsic element. Based on the research result, it can be concluded thathe social conflicts can be found in Saiful Ardi Imam’s Bidadari Paderi that the writer toconvey to readers. The social conflict is between the Adat and the Pendekar groups withthe Paderi. Sutan Pamuncak, who was from the Pendekar group, refused Imam Mudo’srequest to join the Paderi. However , this particular social conflict can be overcome due tothe emergence of the next conflict, namely the social conflict between the Paderi and theHolland troops that want to conquer Minangkabau area. At 1822, as a result the warhappened between them.